THE INVESTIGATION THROUGH STRUCTURAL EQUIVALENCE MODELLING: THE EFFECT OF BEING A UNION MEMBER ON WORK VALUES AND BEHAVIOURS - BAYAR, Levent Serhat (International Journal of Contemporary Economics and Administrative Sciences, 2016)
<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-GB">The aim of this study is to put forward the effect of belonging to a labor union on work values and work behaviours. According to a study conducted on 410 workers, the effect of being solely a member of a labor union on work values and behaviours could not be determined. However, the direct and positive effect of loyalty to a labor union on work behaviours and values was detected. Moreover, it was found out that workers who are members of a labor union pay importance to “Creativity”, which is one of the lower dimensions of work values; nevertheless, workers who are not members of a labor union place importance to “economical advantage and Supervisory Relations”.